Head Bobber: An Insertional Mutation Causes Inner Ear Defects, Hyperactive Circling, and Deafness - Somma, Giuseppina (Springer-Verlag, 2012)
The head bobber transgenic mouse line, produced by pronuclear integration, exhibits repetitive head tilting, circling behavior, and severe hearing loss. Transmitted as an autosomal recessive trait, the homozygote has vestibular and cochlea inner ear defects. The space between the semicircular canals is enclosed within the otic capsule creating a vacuous chamber with remnants of the semicircular canals, associated cristae, and vestibular organs. A poorly developed stria vascularis and endolymphatic duct is likely the cause for Reissner’s membrane to collapse post-natally onto the organ of Corti in the cochlea. Molecular analyses identified a single integration of ~3 tandemly repeated copies of the transgene, a short duplicated segment of chromosome X and a 648 kb deletion of chromosome 7(F3). The three known genes (Gpr26, Cpxm2, and Chst15) in the deleted region are conserved in mammals and expressed in the wild-type inner ear during vestibular and cochlea development but are absent in homozygous mutant ears. We propose that genes critical for inner ear patterning and differentiation are lost at the head bobber locus and are candidate genes for human deafness and vestibular disorders. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10162-012-0316-5) contains supplementary material, which is available to authorized users.